From Rigid to Moderate Salafism: Paths of (Re-)Conversion to Islam among Activists of a Muslim Organisation in Switzerland - Sheikhzadegan, Amir (Journal of Muslims in Europe, 2020)
Defining re-conversion as the re-embracement of one’s (neglected) faith, this article deals with the question of what relations can be identified between conversion/re-conversion to a Salafist reading of Islam, on the one hand, and life course circumstances, identity transformation, and social network features of the individuals concerned, on the other. Combining narrative, autobiographical interviews with qualitative social network analysis, four activists of a Muslim organisation in Switzerland known for its Salafist orientation are portrayed. The comparative analysis shows that, despite sharing the same approach to Islam, the four cases exhibit different modes of the impact of life course and social network on spiritual transformation and vice versa. The paper also discusses the term Salafism and its applicability to the interviewees.